2011
DOI: 10.1002/ca.21098
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the ilioinguinal and iliohypogastric nerves with observations of their spinal nerve contributions

Abstract: Proper anesthesia and knowledge of the anatomical location of the iliohypogastric and ilioinguinal nerves is important during hernia repair and other surgical procedures. Surgical complications have also implicated these nerves, emphasizing the importance of the development of a clear topographical map for use in their identification. The aim of this study was to explore anatomical variations in the iliohypogastric and ilioinguinal nerves and relate this information to clinical situations. One hundred adult fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
3
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 35 publications
(49 reference statements)
0
59
3
3
Order By: Relevance
“…The ilioinguinal nerve also courses over the quadratus lumborum muscle, along the inferior aspect of the iliohypogastric nerve, sending branches to the iliohypogastric nerve. Subsequently, the ilioinguinal nerve pierces the lateral abdominal wall and runs medially to the level of the inguinal ligament (10,11). The sizes of the ilioinguinal and iliohypogastric nerves are inversely proportional to one another.…”
Section: Iliohypogastric and Ilioinguinal Nervesmentioning
confidence: 99%
“…The ilioinguinal nerve also courses over the quadratus lumborum muscle, along the inferior aspect of the iliohypogastric nerve, sending branches to the iliohypogastric nerve. Subsequently, the ilioinguinal nerve pierces the lateral abdominal wall and runs medially to the level of the inguinal ligament (10,11). The sizes of the ilioinguinal and iliohypogastric nerves are inversely proportional to one another.…”
Section: Iliohypogastric and Ilioinguinal Nervesmentioning
confidence: 99%
“…In a recent study of patients undergoing hernia repair, Al-Dabbagh [1] found that the course of the ilioinguinal and iliohypogastric nerves was only consistent with anatomic texts in 41.8% of cases. Furthermore one or both of these nerves was found to be absent in 7.3% of cases [5]. In the current cadaveric dissection, an atypical pattern of inguinal nerve branches was found.…”
Section: Discussionmentioning
confidence: 50%
“…The inguinal nerves are often found to follow variable patterns of distribution [1,5,6]. In a recent study of patients undergoing hernia repair, Al-Dabbagh [1] found that the course of the ilioinguinal and iliohypogastric nerves was only consistent with anatomic texts in 41.8% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ILIH nerves arise from lumbar plexus in many different ways, as a described Klaassen et al In a study with 100 cadavers, the IL nerve entered the abdominal wall 2.8±1.1 cm medial and 4 ± 1.2 cm inferior to the ASIS, and the IH nerve entered the abdominal wall 2.8 ± 1.3 cm medial and 1.4 ± 1.2 cm inferior to the ASIS [25]. James L Whiteside et al studied the course of ILIH nerves from 11 fresh, frozen cadavers, identifying and mapping thirteen IH and sixteen IL nerves.…”
Section: Discussionmentioning
confidence: 99%